Hakikat Peserta Didik Dalam Perspektif Filsafat Pendidikan Islam - Linda Damayanti; Khairunnisa Khairunnisa; Salsabila Saragih; Trisna Pratiwi Hasibuan (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to explain the Nature of Learners in the Perspective of Islamic Education Philosophy to the duties and obligations of students as well as student personality characteristics. This study uses a qualitative approach with the method of literature review. The object of the study is to examine several relevant journals and books related to the problem to be solved. Based on this research, it is hoped that teachers will be able to understand the various characteristics found in their students. Thus, teachers can easily guide their students as better individuals.